Correction: An antibody–supermolecule conjugate for tumor-specific targeting of tumoricidal methylated β-cyclodextrin-threaded polyrotaxanes. Issue 32 (30th July 2020) - Nishida, Kei; Tamura, Atsushi; Kang, Tae Woong; Masuda, Hiroki; Yui, Nobuhiko
Abstract : Correction for 'An antibody–supermolecule conjugate for tumor-specific targeting of tumoricidal methylated β-cyclodextrin-threaded polyrotaxanes' by Kei Nishida et al., J. Mater. Chem. B, 2020, DOI: ; 10.1039/d0tb00575d .